Estrutura populacional de Petrolisthes armatus (Decapoda: Porcellanidae) em recifes de Sabellariidae no litoral Amazônico - CARDOSO, Edma Mayara Pereira (2019)
The populational structure and reproductive features of the anomuran Petrolisthes armatus were studied on a Sabellaria wilsoni (Polychaeta: Sabellariidae) reef at a sandy beach in Algodoal-Maiandeua Island, northeast of Pará. During a year (May 2008 to April 2009) monthly samplings were carried out on a reef zone (900 m²). On each month, 16 fragments were removed with a cylindrical sampler (10 cm diameter and 30 cm height). Samples had their volumes measured and then packed in plastic bags, labeled and fixed with saline formalin 5%. In laboratory, the reef fragments were separated on a sieve (0.3 mm of mesh size) and the organisms counted and separated. Individuals were sexed and measured (carapace width, CW). For ovigerous females, the eggs were counted and classified according to the embryonic development. A total of 3.536 individuals were analyzed: 1.039 males, 310 non-ovigerous females, 916 ovigerous females and 1.271 juveniles. The sex-ratio was 1,2:1 (males:females), with significant deviation, which may be related with behavioral aspects and differential migration between sexes. Most males were larger than females and were more abundant in the larger (mature) and smaller (immature) size classes. Females were more frequent in intermediate size classes, at which they are considered mature organisms (> CW smallest ovigerous female). When compared to other rocky intertidal habitats, reefs have higher density of organisms and proportion of juveniles. Density was higher in eroded reefs, which were found in the dry season, periods of high temperature and salinity. The estimated fecundity was inferior to that recorded in subtropical and temperate environments, ranging from 8 to 449 eggs, with higher occurrence of ovigerous females in the size class (CW) 5-6 mm. P. armatus presented continuous reproduction with reproduction peaks in the dry period, because of higher temperature and salinity of the water, and the beginning of rainy period, due to the availability of larvae and space for reef’s colonization. The results show that reef environments are important habitats for P. armatus, used during different stages of its life cycle as settlement areas, and for growth and reproduction.